Learning Scenario for Better Understanding of Fairy Tales Using Role-playing and Serious Games Methods - Slavova-Petkova, Stanislava; Dimova, Maria; Luchev, Detelin (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2016)
The paper examines how the understanding of fairy tales of little child could be improved with help of two contemporary learning methods role-playing and serious games. A scenario for non-formal and fascinated study of fairy tales was explained with some actual examples using serious game environment ADAPTIMES.
Keywords: Learning Methods; Fairy Tales; Advanced Learning; Serous Games; Role-playing